2011
DOI: 10.1007/s11894-011-0190-z
|View full text |Cite
|
Sign up to set email alerts
|

Current Approach to the Treatment of Achalasia

Abstract: Achalasia is a primary esophageal motility disorder characterized by aperistalsis and incomplete or absent relaxation of the lower esophageal sphincter (LES). The cause of the disease remains elusive and there is no intervention that improves the esophageal body function. Currently, treatment options focus on palliation of symptoms by reducing the LES pressure. The most effective and well-tolerated treatments continue to be the laparoscopic Heller myotomy and endoscopic pneumatic dilation; however, newer techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…25 The main clinical observation of achalasia is dysphagia to solids and liquids; in people, symptoms also include chest pain, heartburn, and regurgitation. 12 Aspiration pneumonia is a common sequela, as is weight loss, although this typically manifests later in the disease process. Patients with chronic achalasia are also at increased risk of developing esophageal cancer, 8,25 likely due to food stasis leading to bacterial overgrowth and nitrosamine production that causes chronic inflammation and dysplasia.…”
mentioning
confidence: 99%
“…25 The main clinical observation of achalasia is dysphagia to solids and liquids; in people, symptoms also include chest pain, heartburn, and regurgitation. 12 Aspiration pneumonia is a common sequela, as is weight loss, although this typically manifests later in the disease process. Patients with chronic achalasia are also at increased risk of developing esophageal cancer, 8,25 likely due to food stasis leading to bacterial overgrowth and nitrosamine production that causes chronic inflammation and dysplasia.…”
mentioning
confidence: 99%
“…Maksimak et al [9] reported 4 children treated with nifedipine before meals who reported relief of symptoms likely related to a decrease in resting LES pressure. In either children or adults, nifedipine is not a definitive therapy and should only rarely be used as a bridge to relieve symptoms until pneumatic dilatation, Botox injection or myotomy can be performed [5,10] .…”
Section: Medical Therapymentioning
confidence: 99%
“…4 Typical symptoms are dysphagia for both solid and liquid food, chest pain, regurgitation 1,3 and in more advanced stages, loss of weight and malnutrition. Currently, the treatment is based on palliative options that reduce the pressure of lower esophageal sphincter (LES) 5 and relieves the main symptoms of achalasia.…”
Section: Introductionmentioning
confidence: 99%